Nilai Moral pada Novel Ayah dan Sirkus Pohon Karya Andrea Hirata - Kusuma, Anjas Saputra Aji; Marsen, Anwar Mufid; Bagiya, Bagiya (PPJB-SIP (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya)., 2023)
Moral Values in the Novel Ayah and the Tree Circus by Andrea Hirata This study aims to describe the moral values in the novel Ayah and the Circus of Trees by Andrea Hirata. This research is a type of qualitative research. The research design is qualitative descriptive research. The data in this study is in the form of words and sentences that contain moral values. The data source for this research is the novel Ayah and the Circus of Trees by Andrea Hirata. This research data analysis technique was carried out in three stages: data reduction, data presentation, and drawing conclusions. The results of the study show that there are three moral values in the novel Ayah and the Circus of Trees by Andrea Hirata, with nine sub-values. These moral values include (a) the relationship between humans and God, including reciting and being grateful; (b) the relationship between humans and themselves, including patience, never giving up, confidence, and discipline; and (c) human relationships with other humans in the social and environmental spheres. Nature includes keeping promises and being honest.Â